2015
DOI: 10.1515/acs-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Screening of carotenoid-producing Rhodotorula strains isolated from natural sources

Abstract: Carotenoids represent large group of various natural pigments ensuring typical coloration of plants, microorganisms and several animals. It was confirmed by many studies, that consuming these biological active compounds has positive impact for human life. Therefore, they are applied in different industrial fields, such as pharmacy, cosmetic, food, and feed industry. Due to high demand for carotenoids we would like to discover new microorganisms overproducing carotenoids. We focused on yeasts of genus Rhodotoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…A red yeast Rhodotorula sp. KF-104 of plant origin (isolated from vegetative parts of vine) was found to produce a mixture of carotenoids, including β-carotene, γ-carotene, torulene and torularhodin, respectively [25].…”
Section: Exploration Of Native Carotenoid-producing Strainsmentioning
confidence: 99%
“…A red yeast Rhodotorula sp. KF-104 of plant origin (isolated from vegetative parts of vine) was found to produce a mixture of carotenoids, including β-carotene, γ-carotene, torulene and torularhodin, respectively [25].…”
Section: Exploration Of Native Carotenoid-producing Strainsmentioning
confidence: 99%
“…Other carotenoids in the pigment extract could be torulene and torularhodin (according to their retention time in the HPLC analysis). Lycopene is a precursor and branch point for the synthesis of β‐carotene and torulene (Tkačova et al, ). The content of β‐carotene in the biomass of the marine Rhodotorula cultivated with the seaweed extract was very similar to that reported for Rhodotorula sp.…”
Section: Discussionmentioning
confidence: 99%
“…The content of β‐carotene in the biomass of the marine Rhodotorula cultivated with the seaweed extract was very similar to that reported for Rhodotorula sp. KF‐104 (39%) (Tkačova et al, ). Although the metabolic pathway for astaxanthin in Rhodotorula species has been described (Hernández‐Almanza et al ) no reports were found in literature demonstrating the synthesis of astaxanthin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the production of by bioprocesses involving microorganisms whose growth speed is relatively high, can ensure a productivity to the process which makes it advantageous [13,14].…”
Section: Introductionmentioning
confidence: 99%